If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3y + -2) = 5(3y + 2) Reorder the terms: 3(-2 + 3y) = 5(3y + 2) (-2 * 3 + 3y * 3) = 5(3y + 2) (-6 + 9y) = 5(3y + 2) Reorder the terms: -6 + 9y = 5(2 + 3y) -6 + 9y = (2 * 5 + 3y * 5) -6 + 9y = (10 + 15y) Solving -6 + 9y = 10 + 15y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15y' to each side of the equation. -6 + 9y + -15y = 10 + 15y + -15y Combine like terms: 9y + -15y = -6y -6 + -6y = 10 + 15y + -15y Combine like terms: 15y + -15y = 0 -6 + -6y = 10 + 0 -6 + -6y = 10 Add '6' to each side of the equation. -6 + 6 + -6y = 10 + 6 Combine like terms: -6 + 6 = 0 0 + -6y = 10 + 6 -6y = 10 + 6 Combine like terms: 10 + 6 = 16 -6y = 16 Divide each side by '-6'. y = -2.666666667 Simplifying y = -2.666666667
| 6+4m-17g+6m+3g= | | 11-1.5y=x | | 30x+9+9m+14x-3m= | | 4x-5=-2x+16 | | m+15c+(-3m)-4= | | 8-(4x+m)=5(x+6) | | 9m-14-6m+4r+12r= | | 7x+14-2x-5=3x+9+2x | | (x+6)(x+3)=340 | | 4(a+3)=2a-12 | | -25d+2s-7+15s-20d= | | -11a^2b*8ab= | | 7x+14-2x-5=3x | | 7x+14-2x-5=3x | | 5a*a^2= | | 2(x+6)=9x+9-7x+3 | | 3a^2-3a= | | 20j+20j-16m-16m+16= | | 6k-(4k+2)-8+8(2k+2)=0 | | x-5=28 | | 6k-(2k+2)-8+8(2k+2)=10 | | 6k-(4k+2)-8+8(2k+2)=10 | | 10+(-4g)+10-13x-2g+5x= | | 2.75=f-.25 | | 3x-15+10x=13x+20 | | 5y+7=1-7y | | -19m+5-(-m)+c-7c= | | 7x-4+3x+12= | | 7x-4+3x+12=30 | | 3x+(-17)+21f+3x-(-21f)= | | 3y-20+y+40=120 | | 3y-20+y+40=180 |